Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Petalostigma pubescens (commonly known as quinine bush) unripe fruit and leaves. Petalostigma is an Australian Euphorbiaceae genus which consists of 7 species. They grow to between 2 and 10 metres in height and have bright orange fruit (when ripe). Petalostigma species were used extensively by indigenous Australians to treat a myriad of bacterial, fungal and viral diseases.1 P. pubescens bark and fruit decoctions were used extensively by Australian Aborigines as an antiseptic and to treat sore eyes. Fruit were also held in the mouth to relieve toothache.1 Despite its common name, there is no scientific evidence to support the presence of quinine in the fruit or leaves (the common name is presumably due to the extremely sharp bitter flavour of the fruit). Recent studies have confirmed the antibacterial, antifungal and antiviral activity of extracts of the leaves and fruit of this plant.2,3 This photograph was taken at Griffith University, Brisbane, Australia in 2011 by Dr Ian Cock.